The Effect of Probiotics Lactobacillus Reuteri on Levels of Ifn-Γ (Th1) and Il-10 (Th2) Cytokines Cells in Mice Postpartum Induced by Staphylococcus Aureus - Riza Tsalatsatul Mufida (Humanistic Network for Science and Technology (HNST), 2017)
The direct causes of maternal mortality among others bleeding, preeclampsia, long delivery, abortion complications, and infections. Nosocomial infections are caused by Methicillin-Resistant Staphylococcus aureus (MRSA), obtained from infection Staphylococcus aureus and now resistant of antibiotics. The spread of bacterial resistance is existing drugs, pushing for extracting antibacterial source of other materials, such as the use of probiotics. Probiotics is as non-pathogenic microorganisms in food supplementation component, which has health benefits for the prevention and treatment of disease, when it is in sufficient quantities. Probiotics is as immunomodulatory and immunostimulatory, then activate all CD4+ T cells into Th1 (IFN-γ) and Th2 (IL-10) cells.Prove whether the effect of probiotic Lactobacillus reuteri to levels of IFN-γ and IL-10 cytokinecells on the spleen of mice model postpartum induced Stapgylococcus aureus bacteria.The study uses pure posttest-only randomized control-group experimental design which utilizes 40 mice (Balb/c) and gestasional aged 13 days which are divided into 8 sample groups. Dosis Lactobacillus reuteri 1x1010 CFU/mice in 250μl via a oral sonde (a gavaging needle). Dosis Staphyloccus aureus 5x107 CFU/mice in 200μl via spuit without needle per vaginal. The levels of IFN-γ and IL-10 cytokine were analyzed for enzyme linked immunosorbent assay (ELISA) kits. This study showed statistically that is significant in levels of IL-10 cells on the first day postpartum, levels of IL-10 and IFN-γ cytokineon the third day postpartum showed statistically that is no significant. There is influence of probiotic Lactobacillus reuteri on levels of IFN-Ɣ and IL-10 cytokine in mice postpartum induced Staphylococcus aureus.Keyword: Lactobacillus reuteri, Staphylococcus aureus, IL-10, IFN-γ